Lo fantástico literarioy su consideración como género: Revisión de las principales teorías - Méndez Robles, Pedro Salvador (Verbum – Analecta Neolatina, 2013)
The meanings dictionaries attribute to the term fantastic are diverse and its daily usage is unclear. Likewise, its complexity does not get any better when it comes to antagonistic theories formulated around the fantastic and literary counterpart. Under these premises, our work intends to take stock of the main conceptualizing approaches around "the fantastic" in the last half of the present century, making it clear what elements bring them closer or grow them apart. We will also tackle its consideration as a genre as it is an inseparable aspect from its theoretical conceptualization. This is so to the extent that the different theories, although being divergent in many cases, stem from the assumption that "the fantastic" enjoys literary autonomy.